2018
DOI: 10.3145/epi.2018.sep.18
|View full text |Cite
|
Sign up to set email alerts
|

Use of social media for health education and corporate communication of hospitals

Abstract: Chapter 1 Introduction 1 Chapter 2 Existing literature on social media and corporate blogging and microblogging 20 2.1 The Internet 20 2.2 The Web 23 2.3 Web 2.0 24 2.4 Social media 30 2.5 Social networks 51 2.6 Blogs 63 2.7 Microblogs 78 2.8 Social media monitoring and listening 88 2.9 Social media use in crises 93 2.10 Interactivity and engagement 97 Chapter 3 Theoretical literature framing and informing this study 3.1 Social media theory 3.2 Public relations theory, including excellence theory 3.3 Corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 245 publications
(442 reference statements)
0
19
0
Order By: Relevance
“…Comparing the hospital Sant Joan de Dèu Hospital with the Clínica Universidad de Navarra (Spain), Costa-Sánchez and Míguez-González (2018) also confirmed that higher activity on social media does not imply higher levels of interaction with the public. In turn, Medina, Buil and Heath (2016) searched for the Facebook profiles of 300 hospitals in the United States (US) and observed that despite 282 of them maintaining an account, only 13 fulfilled at least 7 of the 10 indicators that were used to measure the quality of their activity on this platform.…”
Section: Introduction and State Of The Questionmentioning
confidence: 57%
See 2 more Smart Citations
“…Comparing the hospital Sant Joan de Dèu Hospital with the Clínica Universidad de Navarra (Spain), Costa-Sánchez and Míguez-González (2018) also confirmed that higher activity on social media does not imply higher levels of interaction with the public. In turn, Medina, Buil and Heath (2016) searched for the Facebook profiles of 300 hospitals in the United States (US) and observed that despite 282 of them maintaining an account, only 13 fulfilled at least 7 of the 10 indicators that were used to measure the quality of their activity on this platform.…”
Section: Introduction and State Of The Questionmentioning
confidence: 57%
“…In addition, there is a greater participation of readers in digital news, in terms of frequency and number of votes and recommendations in social networks (Busto-Salinas, 2017). In this study we wanted to know only the situation of these centers, since communication today is "an added value" for any hospital (Costa-Sánchez, 2011, p. 19) and has reached a point where it is "inevitable" to create these departments in these entities, since "human relations are the basis of public relations" (Kirdar, 2007) and "the scope of 2.0 generates a potential for conversation that hospital institutions should take advantage of to become a source of reference information for their public" (Costa-Sánchez & Míguez-González, 2018). Moreover, for some researchers, this practice in the hospital world has become more recognized, more necessary and more important (Henderson, 2005), even its value has increased (Springston & Weaver Lariscy, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing social media for building a credible brand has become a priority for hospitals (Costa-Sánchez & Míguez-González, 2018). The content disseminated on these platforms determines stakeholder's perceptions about the hospital (Triemstra et al, 2018) as well as its own internal functioning, especially patients-doctors' relationships (Miller, Guidy & Fuemmeler, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Organizations including corporations as well as small businesses ought to be familiar with the digital and mobile technologies (Melewar & Navalekar, 2002). They can use them to on a day-to day basis to forge relationships with different stakeholders including employees, customers, suppliers, investors, media, regulatory authorities and the community at large (Bachmann, 2019;Costa-Sánchez & Míguez-González, 2018;Loureiro & Gomes, 2016), or during crises situations (Krishna & Vibber, 2017;Champoux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%